lim(1+sinx-sin(sinx))^x^-3 x趋于0

来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/09 22:07:26
lim(1+sinx-sin(sinx))^x^-3x趋于0lim(1+sinx-sin(sinx))^x^-3x趋于0lim(1+sinx-sin(sinx))^x^-3x趋于0lim(x->0)(

lim(1+sinx-sin(sinx))^x^-3 x趋于0
lim(1+sinx-sin(sinx))^x^-3 x趋于0

lim(1+sinx-sin(sinx))^x^-3 x趋于0
lim(x->0) (sinx-sin(sinx))/x^3
=lim(x->0) (cosx-cos(sinx)cosx)/3x^2
=lim(x->0) (-sinx+sin(sinx)cos^2x+cos(sinx)sinx)/6x
= 1/6*lim(x->0) {[(-sinx)/x] + [sin(sinx)cos^2 x]/x+[cos(sinx)sinx)/x]}
= 1/6* { -1+1+1 }
= 1/6
lim(x->0) (1+sinx-sin(sinx))^x^(-3)
=lim(x->0) {[1+(sinx-sin(sinx))]^[1/(sinx-sin(sinx))]}^[(sinx-sin(sinx))/x^3]
= e^(1/6)